Designing a Qualitative Model of School Principals’ Performance with a Meritocracy Approach - Khodamoradi, Jafar; Davodi, Rasoul; Shokrollahi, Mahboubeh (AI and Tech in Behavioral and Social Sciences, 2026)
The purpose of this study was to design a qualitative model of school principals’ performance in the Department of Education of Karaj County based on a meritocracy approach. The research method was qualitative and based on grounded theory. The participants included organizational and academic experts related to the research topic, who were selected through purposive sampling. A total of 15 participants were interviewed until theoretical saturation was achieved. Data were collected through semi-structured interviews and analyzed using open, axial, and selective coding. The findings indicated that the qualitative model of school principals’ performance in the Department of Education of Karaj County with a meritocracy approach consists of six dimensions: talent attraction and retention, sufficient job-related information, support for the meritocracy process, awareness and analysis of international educational systems, knowledge management, and facilitation of organizational learning. In addition, 20 components were identified, including creating a platform for knowledge production, improving the psychological climate and organizational atmosphere, increasing efficiency, optimizing processes, better resource management, achieving improved student outcomes, enhancing the learning environment, improving educational quality, increasing educational equity, enhancing the effectiveness and productivity of the educational system, reducing costs, moving toward strategic goals, viewing the school as a learning organization, preventing rent-seeking, promoting meritocracy, developing a culture of citizenship and social responsibility, strengthening trust in the educational system, fostering creativity and innovation, and increasing staff commitment. Overall, 168 indicators were extracted and categorized within the paradigmatic model of the research in the form of causal conditions, contextual conditions, intervening conditions, strategies, and consequences.